Prefrontal cortex white matter tracts in prodromal Huntington disease. Issue 10 (14th July 2015) - Matsui, Joy T.; Vaidya, Jatin G.; Wassermann, Demian; Kim, Regina Eunyoung; Magnotta, Vincent A.; Johnson, Hans J.; Paulsen, Jane S.; PREDICT‐HD Investigators and Coordinators of the Huntington Study Group
Abstract Huntington disease (HD) is most widely known for its selective degeneration of striatal neurons but there is also growing evidence for white matter (WM) deterioration. The primary objective of this research was to conduct a large‐scale analysis using multisite diffusion‐weighted imaging (DWI) tractography data to quantify diffusivity properties along major prefrontal cortex WM tracts in prodromal HD. Fifteen international sites participating in the PREDICT‐HD study collected imaging and neuropsychological data on gene‐positive HD participants without a clinical diagnosis (i.e., prodromal) and gene‐negative control participants. The anatomical prefrontal WM tracts of the corpus callosum (PFCC), anterior thalamic radiations (ATRs), inferior fronto‐occipital fasciculi (IFO), and uncinate fasciculi (UNC) were identified using streamline tractography of DWI. Within each of these tracts, tensor scalars for fractional anisotropy, mean diffusivity, radial diffusivity, and axial diffusivity coefficients were calculated. We divided prodromal HD subjects into three CAG‐age product (CAP) groups having Low, Medium, or High probabilities of onset indexed by genetic exposure. We observed significant differences in WM properties for each of the four anatomical tracts for the High CAP group in comparison to controls. Additionally, the Medium CAP group presented differences in the ATR and IFO in comparison to controls. Furthermore, WM alterations in the PFCC, ATR, and IFO showed robust associations with neuropsychological measures of executive functioning. These results suggest long‐range tracts essential for cross‐region information transfer show early vulnerability in HD and may explain cognitive problems often present in the prodromal stage. Hum Brain Mapp 36:3717–3732, 2015. © 2015 Wiley Periodicals, Inc.